Antibacterial and anticancer activity of loaded quinazolinone polypyrrole/chitosan silver chloride nanocomposite. Issue 6 (13th April 2017) - Salahuddin, Nehal; Elbarbary, Ahmed A.; Alkabes, Hend A.
ABSTRACT: Polypyrrole/chitosan-silver chloride core shell nanocomposite (AgCl@PPC) was prepared by in situ oxidative polymerization of pyrrole (Py) using ferric chloride in the presence of chitosan (CS) and silver nitrate to develop a carrier and controlled release system for 3-amino-2-phenyl-4(3H)-quinazolinone (I). For sake of comparison, polypyrrole chitosan core shell nanoparticles (PPC) were prepared and loaded by (I). Fourier transform infrared spectroscopy, X-ray diffraction and thermal gravimetric analysis confirm that I was loaded into PPC and AgCl@PPC core shell nanocomposites respectively, through physical interaction. Results revealed that loaded AgCl@PPC and PPC exhibited excellent antibacterial and anticancer efficacy against Ehrlich ascites carcinoma cells. GRAPHICAL ABSTRACT: